Overcoming Difficult Science Topics through Alternative Media in Elementary Education - Armawati, Armawati; Vebrianto, Rian; Habibi, Mhmd; Radeswandri, Radeswandri (Journal of Islamic Education Students (JIES), 2025)
Twenty-first century education demands deep conceptual understanding and applied abilities to address the challenges of modern learning. This study aims to identify the main difficulties faced by elementary school students in science subjects and propose relevant solution strategies to enhance learning effectiveness. Employing a mixed-method approach, the research integrates quantitative and qualitative analyses gathered from two IPAS teachers and thirty sixth-grade students through questionnaires, interviews, and observations. Results reveal that two topics ÔÇ£LetÔÇÖs Get to Know Our EarthÔÇØ (63.33%) and ÔÇ£Harmony in LifeÔÇØ (36.66%) are the most challenging, significantly affecting student engagement and comprehension during lessons. Various solution strategies, including the use of Canva media, spinning earth surface visualizations, LKPD worksheets, 3D sociodrama, and interactive animation videos, have demonstrably improved studentsÔÇÖ conceptual understanding and active participation. These findings highlight the importance of innovative media and contextual strategies in supporting more effective and meaningful science learning at the elementary level.